Balanced activities of Hsp70 and the ubiquitin proteasome system underlie cellular protein homeostasis - Jawed, Areeb; Ho, Chi-Ting; Grousl, Tomas; Shrivastava, Aseem; Ruppert, Thomas; Bukau, Bernd; Mogk, Axel (Frontiers in molecular biosciences, 2023)
To counteract proteotoxic stress and cellular aging, protein quality control (PQC) systems rely on the refolding, degradation and sequestration of misfolded proteins. In Saccharomyces cerevisiae the Hsp70 chaperone system plays a central role in protein refolding, while degradation is predominantly executed by the ubiquitin proteasome system (UPS). The sequestrases Hsp42 and Btn2 deposit misfolded proteins in cytosolic and nuclear inclusions, thereby restricting the accessibility of misfolded proteins to Hsp70 and preventing the exhaustion of limited Hsp70 resources. Therefore, in yeast, sequestrase mutants show negative genetic interactions with double mutants lacking the Hsp70 co-chaperone Fes1 and the Hsp104 disaggregase (fes1Δ hsp104Δ, ΔΔ) and suffering from low Hsp70 capacity. Growth of ΔΔbtn2Δ mutants is highly temperature-sensitive and results in proteostasis breakdown at non-permissive temperatures. Here, we probed for the role of the ubiquitin proteasome system in maintaining protein homeostasis in ΔΔbtn2Δ cells, which are affected in two major protein quality control branches. We show that ΔΔbtn2Δ cells induce expression of diverse stress-related pathways including the ubiquitin proteasome system to counteract the proteostasis defects. Ubiquitin proteasome system dependent degradation of the stringent Hsp70 substrate firefly Luciferase in the mutant cells mirrors such compensatory activities of the protein quality control system. Surprisingly however, the enhanced ubiquitin proteasome system activity does not improve but aggravates the growth defects of ΔΔbtn2Δ cells. Reducing ubiquitin proteasome system activity in the mutant by lowering the levels of functional 26S proteasomes improved growth, increased refolding yield of the Luciferase reporter and attenuated global stress responses. Our findings indicate that an imbalance between Hsp70-dependent refolding, sequestration and ubiquitin proteasome system-mediated degradation activities strongly affects protein homeostasis of Hsp70 capacity mutants and contributes to their severe growth phenotypes.